'A Feast for the [Cold-War] Imagination': Liminal Eastern Europe in the Writings of John Updike, Joyce Carol Oates and Philip Roth. (6th August 2022) - Bryla, Martyna
Abstract : Inspired by the well-established trope of Eastern Europe's in-betweenness, this article uses the notion of liminality to explore the images of Eastern Europe during the Cold War in the works of three American authors: John Updike, Joyce Carol Oates and Philip Roth. Not only do these works map Eastern Europe as liminal in the imagological sense of the term, that is, as oscillating between competing narratives of otherness and familiarity; empathy and hostility; the East and the West, but also the very experience of venturing behind the Iron Curtain is charged with potentiality: the Eastern-European cityscape becomes the contact zone between cultures and the locus of self-discovery for the American characters. The resultant imaginative geography is at once contemporary and allochronic; political and personal, as it reiterates the Cold War balance of power while at the same time recycling existing representations of the area and reflecting the authors' sensibilities.